Epiphanius' Alogi and the Johannine controversy : a reassessment of early ecclesial opposition to the Johannine corpus - Manor, T. Scott. (Vigiliae Christianae, Supplements, 2016)
In this work T. Scott Manor provides a new perspective on a common view, known as the 'Johannine Controversy', which maintains that the early church once tried to jettison the Gospel and Apocalypse of John as heretical forgeries. Primary evidence comes from Epiphanius of Salamis, who mentions a heretical group with such views, the Alogi . This along with with other evidence from sources including Irenaeus, Hippolytus, Origen, Eusebius, Photius, Dionysius bar Salibi, Ebed-Jesu and others has led to the conclusion that a certain Gaius of Rome led the Alogi in this anti-Johannine campaign. By carefully examining Epiphanius' account in relation to these other sources, Manor arrives at very different conclusions that question whether any such controversy ever existed at all.